Hb Milano [α109(G16)Leu→Pro (CTG>CCG); HBA1: c.329T>C]: A Novel Variant on the α1-Globin Gene in an Italian Family. (2nd January 2019) - Curcio, Cristina; Giannone, Valentina; Benzoni, Elena; Cesaretti, Claudia; Ivaldi, Giovanni
Abstract: Interest in α-globin point mutations has increased in the past few years because nondeletional variations can affect protein function and stability, giving rise to hemoglobin (Hb) variants that present a wide spectrum of phenotypes, from asymptomatic forms to hemolytic anemia. We describe a novel α1-globin gene variant, which we have named Hb Milano [α109(G16)Leu→Pro (C T G>C C G); HBA1 : c.329T>C]. We performed high performance liquid chromatography (HPLC) to carry out Hb analysis, capillary electrophoresis (CE) for Hb separation and quantitation of Hb subtypes, two tests on stroma-free lysates for evaluating Hb stability, multiplex ligation-dependent probe amplification (MLPA) to detect deletions/duplications within the α gene cluster and Sanger sequencing of the α-globin genes. No abnormal Hb variants were identified by HPLC and CE. Isopropanol and stability tests were negative. The peripheral blood film showed no inclusions such as Hb H or Heinz bodies. Multiplication ligation-dependent probe amplification of the α-globin gene cluster detected a heterozygosity for the −α 3.7 (rightward) deletion. Direct sequencing of the α-globin genes identified the Hb Milano variant on the HBA1 gene. No mutations were found on the HBA2 gene. The clinical consequences of the Hb Milano variant differ based on the genotype: according to our study, the hematological parameters range from a marked microcythemia with mild anemia if the variant is coinherited with an α gene deletion, to mild microcytosis when the variant is not associated with α gene deletions.